Strategy of the Indonesian Waqf Education Foundation (YEWI) in Increasing the Cash Waqf Literacy Index in Indonesia - Zainal Mukhid (Finance : International Journal of Management Finance, 2023)
This research is motivated by the author's interest in looking at non-governmental institutions that have made a major contribution in socializing waqf literacy, educating waqf other than the Indonesian Waqf Board (BWI). The institution in question is the Indonesian Waqf Education Foundation (YEWI), which was founded in 2014 in Yogjakarta. As an institution that also meets with the Indonesian Waqf Board, the Indonesian Waqf Education Foundation (YEWI) has programs that prevent the same thing, but focus more on increasing literacy and involvement in the waqf community. This research uses descriptive qualitative methods. Researchers interviewed 3 YEWI administrators and several alumni who participated in training held by YEWI. Data shows that 1) Indonesia has the largest Muslim population in the world, but the realization of waqf is still small. 2) Waqf has not functioned optimally as a solution to solving the problem of economic empowerment as expected by Islamic sharia, so that the effect of improving the economy has not been felt by the community. 3) The level of public literacy regarding waqf issues is still low, so that public enthusiasm or awareness of waqf is still low. The researcher concluded that the waqf education strategy carried out by YEWI in order to increase the waqf literacy index in Indonesia was by forming several work units, namely: a) Duta Waqf Institute, b) Waqf Consulting and Planning Bureau, c) Duta Wakaf Networks, and d) Social Indonesia Preneur Association (INSANI). Second, YEWI has prepared work programs, namely: a) Waqf Ambassador Professional Program, b) Waqf Literacy Program, c) Waqf Participation Program.